Legal Regulations Pertaining to Product Safety and Quality Standards in MSMEs Business in Indonesia - Khuan, Hendri; Judijanto, Loso; Juminawati, Sri (The Easta Journal Law and Human Rights, 2024)
This research delves into the multifaceted landscape of intellectual property protection within the Indonesian creative industries. Through qualitative analysis, interviews with 10 key informants elucidated the challenges faced by businesses, including rampant piracy, inadequacies in legal frameworks, and enforcement issues. Businesses responded with diverse legal strategies, encompassing copyright protection, trademark registration, industry collaboration, and technological solutions. Case studies provided tangible examples, showcasing the effectiveness and challenges of these strategies. Recommendations for legislative reforms, strengthened enforcement mechanisms, industry collaboration, and technological innovation are proposed. This research contributes valuable insights into the dynamic interplay between legal challenges and strategic responses in safeguarding intellectual property within the vibrant Indonesian creative industries.